The Influence of Using Crossword Puzzle Towards the Students’ Vocabulary Mastery - Ria Anggelia Tambun (Bandar Lampung University (UBL), 2014)
The objective of this research was to find out the influence of using crossword puzzle towards the students’ vocabulary mastery at grade seven of SMP PGRI 6 Bandar Lampung.Data collection was conducted through two pre-tests and two pos-tests for experimental group and control group. Treatment using crossword puzzle was administered for experimental group and traditional teaching was applied for the control group.Data analysis was attempted using t-Test for two group design. Result indicated that p-value 1%= 2.64, 5%= 1.99 and t-value= 7.620. It meant that the result was statistically significant because p-value was smaller than t-value. Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted.Based on the data analysis, the writer concluded that there was influence of using crossword puzzle towards the students’ vocabulary mastery at grade seven of SMP PGRI 6 Bandar Lampung.